Implementasi Nilai-Nilai Pancasila dalam Menanggulangi Pelecehan Seksual di Lingkungan Masyarakat - Dea Pitaloca; Nasywa Iedha Khaerunisa Anrose; Nadia Aristawati Daniswara; Maulia Depria Kembara (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Sexual harassment, which jeopardizes human rights and poses a threat to individual’s well-being within society, is a type of violence. The increasing prevalence of sexual harassment cases has become a crucial societal concern, as it can transpire indiscriminately. This study intends to elucidate how Pancasila is implemented to address sexual harassment in the community. Pancasila, as the fundamental principles of the Indonesian state, encompasses pertinent values such as justice, unity, equality, and humanity, which serve as a foundation for combating sexual harassment. The research methodology employed entails a literature review incorporating library studies.